Santam : crop insurance and climate change - Rosenthal, Jean, (SAGE knowledge. Cases., 2016)
Santam, the leading short-term insurer in South Africa, was pursuing a strategy to build climate change resilience in South Africa. In particular, the company was taking a look at its crop insurance business. Santam faced considerable challenges in this area as growers in much of Africa had not been interested in insurance in the past. How could the company make crop insurance more feasible? And how could the company share its expertise in risk management and mitigation to benefit Africa in the face of climate change?